2015
DOI: 10.1021/acs.chemrestox.5b00336
|View full text |Cite
|
Sign up to set email alerts
|

Study of Bioreductive Anticancer Agent RH-1-Induced Signals Leading the Wild-Type p53-Bearing Lung Cancer A549 Cells to Apoptosis

Abstract: quinone oxidoreductase (NQO1) which reduces this diaziridinylbenzoquinone into DNA-alkylating hydroquinone and is overexpressed in many tumors. Another suggested mechanism of RH-1 toxicity is the formation of reactive oxygen species (ROS) arising from its redox cycling. In order to improve anticancer action of this and similar antitumor quinones, we investigated the involvement of different signaling molecules in cytotoxicity induced by RH-1 by using wild-type tumor suppressor p53 bearing nonsmall cell lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 100 publications
1
5
0
Order By: Relevance
“…An AO/EtBr staining assessment depends on nuclear morphology and is specific for apoptosis and necrosis. AO/EtBr staining showed that live cells demonstrated ordinary nuclear staining and green chromatin with organized structures; however, apoptotic cells contained fragmented chromatin (orange) 28. Our results are in excellent agreement with those suggesting that MTX could influence MMP, resulting in cell death (Figure 4).…”
Section: Discussionsupporting
confidence: 89%
“…An AO/EtBr staining assessment depends on nuclear morphology and is specific for apoptosis and necrosis. AO/EtBr staining showed that live cells demonstrated ordinary nuclear staining and green chromatin with organized structures; however, apoptotic cells contained fragmented chromatin (orange) 28. Our results are in excellent agreement with those suggesting that MTX could influence MMP, resulting in cell death (Figure 4).…”
Section: Discussionsupporting
confidence: 89%
“…To test whether any residual NQO1 or NQO2 activity in MDA-P or MDA-R contributes to RH1 reduction, we measured NQO1 and NQO2 enzyme substrate consumption kinetic rates in cell lysates. A549 cell line known for high NQO1 activity contributing to RH1 toxicity [22] was used as a positive control. Our data show that both cell lines demonstrate no observable NQO1 activity (Figure 1E) and there is no statistically significant difference between NOQ2 activity in MDA-P and MDA-R cells (Figure 1F).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, depending on the molecules, such DNA damage can be caused by the parent form or following its metabolic conversion to electrophilic or radical species [5]. In this context, quinones having redox-cycling properties are endowed with potential anticancer activities [1][2][3][4][5][6][7][8][9]. The rationale behind this is based on a particular ambivalence of cancer cells: they produce a large amount of reactive oxygen species (ROS), while they are generally deficient in antioxidant enzymes [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%